Quantifying the effect of dobutamine stress on myocardial Pi and pH in healthy volunteers: A 31P MRS study at 7T. Issue 3 (14th September 2020) - Apps, Andrew; Valkovič, Ladislav; Peterzan, Mark; Lau, Justin Y. C.; Hundertmark, Moritz; Clarke, William; Tunnicliffe, Elizabeth M.; Ellis, Jane; Tyler, Damian J.; Neubauer, Stefan; Rider, Oliver J.; Rodgers, Christopher T.; et al.
Abstract : Purpose: Phosphorus spectroscopy ( 31 P‐MRS) is a proven method to probe cardiac energetics. Studies typically report the phosphocreatine (PCr) to adenosine triphosphate (ATP) ratio. We focus on another 31 P signal: inorganic phosphate (Pi), whose chemical shift allows computation of myocardial pH, with Pi/PCr providing additional insight into cardiac energetics. Pi is often obscured by signals from blood 2, 3‐diphosphoglycerate (2, 3‐DPG). We introduce a method to quantify Pi in 14 min without hindrance from 2, 3‐DPG. Methods: Using a 31 P stimulated echo acquisition mode (STEAM) sequence at 7 Tesla that inherently suppresses signal from 2, 3‐DPG, the Pi peak was cleanly resolved. Resting state UTE‐chemical shift imaging (PCr/ATP) and STEAM 31 P‐MRS (Pi/PCr, pH) were undertaken in 23 healthy controls; pH and Pi/PCr were subsequently recorded during dobutamine infusion. Results: We achieved a clean Pi signal both at rest and stress with good 2, 3‐DPG suppression. Repeatability coefficient (8 subjects) for Pi/PCr was 0.036 and 0.12 for pH. We report myocardial Pi/PCr and pH at rest and during catecholamine stress in healthy controls. Pi/PCr was maintained during stress (0.098 ± 0.031 [rest] vs. 0.098 ± 0.031 [stress] P = .95); similarly, pH did not change (7.09 ± 0.07 [rest] vs. 7.08 ± 0.11 [stress] P = .81). Feasibility for patient studies was subsequently successfully demonstrated in a patient with cardiomyopathy. Conclusion: We introduced a method that can resolve Pi using 7 Tesla STEAM 31 P‐MRS. We demonstrate the stability of Pi/PCr and myocardial pH in volunteers at rest and during catecholamine stress. This protocol is feasible in patients and potentially of use for studying pathological myocardial energetics.